Al-Quran, Thibaq, Muqabalah - Suhaimi, Suhaimi (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2020)
The Koran was revealed in Arabic. This has been emphasized by Allah Ta`ala himself by mentioning the arabiyyan quranan. From that, the Arabic language used by Allah in Al-Quan must be understood and believed to have its own specialties over other languages in the world. In studies related to various branches of Arabic, there are various terms, including thibaq and muqabalah. These two terms are known in the study of the Balaghah wa bil branch of science specifically badi` science. Although these two terms are both related to the beauty of meaning or tahsin of meaning, thibaq and muqabalah also have differences, thibaq is more about the gathering of two opposing things, whereas muqabalah can be in the form of collecting more than two opposing meanings and it can also be other than that. . Because the Al-Quran is in Arabic, of course it is not silent from the two things that are part of the meaning of the tahsin, especially since the Koran is the holy Kalam whose beauty exceeds the beauty of the language used by Arabic linguists throughout the ages. The meaning of tahsin in the form of thibaq and muqabalah in the Koran is quite widely scattered in various letters and verses. This is certainly not a coincidence, but a clear proof that the Koran has the advantage of a language style which is quite beautiful and interesting.